Gabungan Ekstrak Rimpang Temulawak, Daun Tanjung, dan Daun Belimbing Manis Berdasarkan Electrocardiogram Berpotensi Sebagai Antiaritmia pada Kucing - Rahminiwati, Min; Safitri, Widia; Noviana, Deni (Jurnal Veteriner; Vol 20 No 3 (2019)DO - 10.19087/jveteriner.2019.20.3.409, 2019)
Mimusops elengi L. , Averrhoa carambola L. and Curcuma xanthorrihiza Roxb singly were reported to have hypothensif effect. Mechanism underlying decrease of blood pressure was suggested through modification of cardiac activity. The Effect of Mimusops elengi L., combined with Averrhoa carambola L. and Curcuma xanthorrihiza Roxb extract on cardiac activity were studied using ECG on 12 male cats that were grouped to be a control group administered aquadestilata, and treatment group administered extract of 21 mg and 82 mg/2 kg bw orally respectively. The extracts were given 3 h prior to ECG. The results showed a decrease in P wave, QRS complex and the speed of the heart rate after administration of combination of extract . However QT and PR intervals were increased. This showed that the extract can weaken a contraction of the Atria and ventricles, prolonging the onset of the occurrence of atrial contraction towards ventricular contraction, extending the onset of contraction and relaxation of the ventricles and cause a decrease in heart rate. Based the cardiogram, It was concluded that their combination is valuable for treatment of aritmia.